Preparation method of spray for traumatic injuries - WANG YONG (2017)
The invention relates to a preparation method of spray for traumatic injuries. The spay for the traumatic injuries is obtained by preparing raw materials, soaking in ethanol liquid and mixing. The spray for the traumatic injuries is mainly used for treating all kinds of traumatic injuries such as closed soft tissue contusion, fracture and dearticulation local swelling and pain, trauma local wound bleeding and stenosing tenovaginitis of flexor digitorum and also can be used for treating rheumatic arthritis, gouty arthritis and cellulitis. 种跌打喷雾剂的制备方法，通过原料制备和在乙醇液体中的浸泡混合制得，该喷雾剂主治各种跌打损伤如：闭合性软组织挫伤、骨折及关节脱位局部肿痛、外伤局部伤口出血、屈指肌腱狭窄性腱鞘炎等，亦可治疗风湿性关节炎，痛风性关节炎，蜂窝组织炎。